Perceptions of brachyfacial, mesofacial and dolichofacial individuals with regard to the buccal corridor in different facial types - Matheus Melo PITHON; Kayure Rocha da MATA; Karina Silva ROCHA; Brenda do Nascimento COSTA; Fernando NEVES; George Caique Gouveia BARBOSA; Raildo da Silva COQUEIRO (University of São Paulo, 2014)
Objective: Evaluate the esthetic perception and attractiveness of the smile with regard to the buccal corridor in different facial types by brachyfacial, mesofacial and dolichofacial individuals. Material and Methods: The image of a smiling individual with a mesofacial type of face was changed to create three different facial types with five different buccal corridors (2%, 10%, 15%, 22% and 28%). To achieve this effect, a photo editing software was used (Adobe Photoshop, Adobe Systems Inc, San Francisco, CA, EUA). The images were submitted to evaluators with brachyfacial, mesofacial and dolichofacial types of faces, who evaluated the degree of esthetic perception and attractiveness by means of a visual analog scale measuring 70 mm. The differences between evaluators were verified by the Mann-Whitney test. All statistics were performed with a confidence level of 95%. Results: Brachyfacial individuals perceived mesofacial and dolichofacial types of faces with buccal corridor of 2% as more attractive. Mesofacial individuals perceived mesofacial and dolichofacial types of faces with buccal corridor of 2%, 10% and 15% as more attractive. Dolichofacial individuals perceived the mesofacial type of face with buccal corridor of 2% as more attractive. Evaluators of the female sex generally attributed higher scores than the male evaluators. Conclusion: To achieve an enhanced esthetic smile it is necessary to observe the patient's facial type. The preference for narrow buccal corridors is an esthetic characteristic preferred by men and women, and wide buccal corridors are less attractive.